A luminescent terbium(iii) probe as an efficient 'Turn-ON' sensor for dipicolinic acid, a Bacillus Anthracis biomarker. (14th September 2022) - Yadav, Usha; Abbas, Zafar; Butcher, Ray J.; Patra, Ashis K.
Abstract : This work drives the potential of lanthanide luminescence in the quantification and detection of the B. Anthracis bacterial spore by targeting dipicolinic acid (DPA), a principal component of anthrax spores. Abstract : Extremely hazardous Bacillus Anthracis bacterial endospores comprise dipicolinic acid (DPA) as a universal and major constituent (10 15 molecules per spore, 1 M), which acts as a prominent biomarker. Such highly infectious and lethal pathogens could be maliciously used as biothreat agents or bioweapons in spreading bioterrorism, posing a serious threat to public health and national security. Therefore, a sensitive, selective, and efficient detection or surveillance system is needed to combat the threats of bioterrorism events. Herein, we designed an efficient detection strategy based on a DPA-sensitized time-resolved luminescent (TRL) TbL -probe formulated as [Tb( p -BrPTC)(H2 O)3 ](OTf), where p -BrPTC = 4′-(4-bromophenyl)-[2, 2′:6′, 2′′-terpyridine]-6, 6′′-dicarboxylic acid. Our investigation showed an instant optical response of ∼600-fold enhancement in the luminescence intensity of the 5 D4 → 7 F5 band upon the equimolar addition of the DPA 2− biomarker, and the probe eventually acted as a 'Turn-ON' sensor. We successfully recognized and provide evidence of DPA 2− coordination to the poorly luminescent TbL-probe, resulting in the formation of a strongly luminescent and coordinatively saturated rigid complex whose formation was validated by 1 H-NMR titration, TRL titration, and ESI-MS analysis. Further, the DPA 2− sensing mechanism was supported by monitoring the luminescence excited state lifetime ( τ ) increase from 140 μs to 1.41 ms; such a great enhancement strongly suggests their coordination to the TbL-probe. Additionally, the luminescence titration data presents the strong binding affinity of the DPA 2− biomarker towards the Tb(iii )-probe ( K b = 6.67 × 10 6 M −1 ), making it a highly sensitive and selective sensor. Interestingly, the luminescence response prevails even in the presence of competitive phosphate anions in aqueous media relevant to physiological samples. Most notably, the TRL response of the TbL-probe was found to be highly selective for the DPA 2− biomarker in the presence of various interfering carboxylic acids, amino acids, and several other bio-analytes, and it could quantitatively detect DPA 2− up to ∼54 ppb (0.32 μM). Overall, the results are quite promising for developing reliable, rapid, and sensitive Ln(iii )-based time-resolved luminescence (TRL) probes for anthrax spore detection, and expandable to other biothreat agents having chemically fitting biomarkers for interactions with Ln(iii ) receptors.